Blockade of adrenergic β‐receptor activation through local delivery of propranolol from a 3D collagen/polyvinyl alcohol/hydroxyapatite scaffold promotes bone repair in vivo. (20th November 2019) - Wu, Hao; Song, Yue; Li, Junqin; Lei, Xing; Zhang, Shuaishuai; Gao, Yi; Cheng, Pengzhen; Liu, Bin; Miao, Sheng; Bi, Long; Yang, Liu; Pei, Guoxian
Abstract: Objectives: Activation of the sympathetic system and adrenergic β‐receptors following traumatic bone defects negatively impairs bone regeneration. Whether preventing β‐receptor activation could potentially improve bone defect repair is unknown. In this study, we investigated the effect of systematic administration and local delivery of propranolol through composite scaffolds on bone healing. Materials and methods: Collagen/PVA/propranolol/hydroxyapatite（CPPH）composite scaffolds were fabricated with 3D printing technique and characterized by scanning electron microscope (SEM). Micro‐CT analysis and bone formation histology were performed to detect new bone formation. Osteogenic differentiation of bone marrow stromal cells (BMSCs) and osteoclastogenesis of bone marrow monocytes cultured with scaffolds extract were performed for further verification. Results: Intraperitoneal injection of propranolol did not significantly improve bone repair, as indicated by micro‐CT analysis and bone formation histology. However, CPPH scaffolds exhibited sustained release of propranolol in vitro and significantly enhanced bone regeneration compared with vehicle collagen/PVA/hydroxyapatite (CPH) scaffolds in vivo. Moreover, in vitro experiments indicated the scaffolds containing propranolol promoted the osteogenic differentiation and migration of rat BMSCs and inhibited osteoclastogenesis by preventing β‐receptor activation. Conclusions: This study demonstrates that local adrenergic β‐receptor blockade can effectively enhance the treatment of bone defects by stimulating osteogenic differentiation, inhibiting osteoclastogenesis and enhancing BMSCs migration.